The Customs Tariff = التعريفة الجمركية / Presidency - Egypt. Presidency (2025)
live animals : animal products -- 2. vegetable products -- 3. animal or vegetable fats and oils and their fats: animal or vegetable waxes -- 4. prepared foodstuffs: beverages, spirits and vinegar; tobacco and manufactured tobacco substitutes -- 5. mineral products -- 6. products of the chemical or allied industries -- 7. plastics and articles thereof: rubber and articles thereof -- 8. raw hides and skins, leather, furskins and articles thereof: saddlery and harness: travel goods, handbags and similar containers; articles of animal gut (other then silk-worm gut) -- 9. wood and articles of wood: wood charcoal cork and articles of cork : manufacture of straw, of esparto or of other plaiting materials : Basketware and wickerwork 10. pulp of wood or of other fibrous cellulosic material : recovered (waste and scrap) paper or paperboard : paper and paperboard and articles thereof -- 11. textiles and textile articles footwear, headgear, umbrellas, sun umbrellas, walking-sticks, seat-sticks, whips, riding-crops and parts thereof : feathers and articles made therewith : atrificial flowers : articles of human hair -- 12 articles of stone, plaster materials : ceramic products : glass and glassware -- 13. natural or cultured pearls, precious or semi- precious stones, precious metals, metals clad with precious metal and articles thereof : imitation jewellery : coin -- 14 base metal and articles of base metal 15. mechinery and mechanical appliances : electrical equipment : parts thereof : sound Recorers and reproducers, television image and sound recorders and reproducers and parts and accessories of such articles -- 16. vehicles, aircraft, vessels and associated transport equipment -- 17.Optical, photographic, cinematographic, measuring, checking, precision, medical or surgical instruments and apparatus: clocks and watches: musical instruments: parts and accessories thereof -- 18. arms and ammunition: parts and accessories thereof -- 19. miscellaneous manufactured articles -- 20. works of art, collector's pieces and antique